O jogo escape room: olhares interdisciplinares de uma ferramenta mediadora no processo educativo - Santos, Kamilla Katinllyn Fernandes dos (2021)
Countless dimensions permeate the way we teach and learn in school, although one of these seems to have a more direct impact on the deepening degree of learning: mediation of content. It is always necessary to seek proposals for the methodological approach that integrate intellectual activity. We glimpse in games that, undeniably, are part of the daily life of young people/digital natives, a possibility of constituting spaces for interaction, experiences and learning. In this sense, our research has the general objective of analyzing the Escape Room game as an interdisciplinary mediating tool in the educational process. For that, we started from a mixed methods research, having combined the qualitative and quantitative approaches and we carried out an action research, in which the methodological paths took place in the construction of a framework, implementation of the game and application of questionnaires in an IFRN teacher training course - Ipanguaçu Campus. To articulate our first theoretical section, we used Vygotsky's studies (1989, 1996, 1998, 2000, 2001) to understand the concepts of the Zone of Proximal Development, learning in the social context and the role of mediation. In the second theoretical section, in which we reveal the game that is the object of this study, we used the studies by Foncubierta and Rodríguez (2015) to define the constituent elements of the game, Murray (2015) in the construction of the elementary matrix of agency, immersion and transformation, Whitton (2018) to discuss the conceptual aspects, Berzosa (2018) to address the skills and Santos and Moura (2011) in the elaboration of the escape. The results show that the game stimulated linguistic, logical-mathematical, spatial, musical, corporal, naturalistic, intrapersonal and interpersonal intelligences, awakened varied lines of stimulation, brought together different thematic axes, made it possible to learn conceptual, procedural and attitudinal contents, it increased all the elements that make up a serious game and stimulated tangent learning